The Anatomical Basis of Nonuniform Settlement of the C2 Lateral Mass and Its Association With Atlantoaxial Osteoarthritis - Chao Tang; Chen Hui Cai; Ying Zhang; Ye Hui Liao; Xian Ming Huang; Xu Zhao; De Jun Zhong; Tong Wei Chu (Orthopaedic Surgery, 2025)
ABSTRACT Objective Studies have described the nonuniform settlement of C2 lateral mass (C2LM‐NUS) as an asymmetrical change of the bilateral C2 lateral masses. This study aimed to: (1) identify the objective evidence for the C2LM‐NUS and clarify its anatomical basis; (2) explore the association between C2LM‐NUS and atlantoaxial osteoarthritis (AAOA), and verify the related biomechanics. Methods Seventy‐nine dry axis specimens were measured macroscopically. The vertical distance between the superior articular surface and the lower edge of the vertebra was defined as the settlement value of C2 lateral mass (C2LMS). Twelve formalin‐embalmed axis specimens were scanned using micro‐computed tomography (Micro‐CT), and the trabecular microstructure of lateral masses was analyzed. 522 patients who underwent a head and neck or cervical spine CT scan were reviewed. The C2LMS was measured, and the bilateral difference (d‐C2LMS) was calculated. The AAOA was recorded. Normal and C2LM‐NUS upper cervical spine (C0‐C3) finite element models were established. The stress distributions on the alar ligament, transverse ligament, and lateral mass cartilage were analyzed using Abaqus software under varying torque conditions. Results Macroscopic analysis revealed that the C2LMS measured at the center point was comparable to the overall C2LMS (18.19 ± 1.83 mm vs. 18.18 ± 1.82 mm, p = 0.942). Twenty‐seven dry axis specimens (34.2%) were identified as C2LM‐NUS because they showed significant differences in bilateral C2LMS (d‐C2LMS: 1.21 ± 0.32 mm). Micro‐CT analysis revealed that four formalin‐embalmed axis specimens with C2LM‐NUS exhibited a substantial difference in trabecular microstructural parameters between the settlement and the normal lateral masses. Clinical observations indicated that C2LM‐NUS was an independent risk factor for AAOA (adjusted odds ratio = 2.041, p < 0.001). Finite element analysis revealed that in the C2LM‐NUS model, the maximum stress on the settlement side of the alar ligament increased by 47.4%–53.3% compared to the opposite side, and the cartilage stress increased by 15.0%–68.5%. Meanwhile, the maximum stress of the transverse ligament in the C2LM‐NUS model was 1.3–1.6 times greater than that of the normal model. Conclusions The macroscopic measurement of the axis specimens provided objective anatomic evidence for C2LM‐NUS. Micro‐CT showed that C2LM‐NUS was associated with asymmetrical alterations of the trabecular microstructure of the lateral masses, suggesting that it is a pathological change rather than a normal phenomenon. The clinical study indicated that C2LM‐NUS is an independent risk factor for AAOA. Stress concentration in unilateral alar ligaments and articular cartilage is a biomechanical contributor to AAOA.